Design and application of flotation systems for the treatment of reinjected water in a Colombian petroleum field - Forero, Jorge Enrique; Ortiz, Olga Patricia; Duque, José Javier (CT&F - Ciencia, Tecnología y Futuro, 2007)
This document presents the application of a new flotation process, developed by Ecopetrol S.A., for the treatment of produced or residual production waters for injection. Recently, treatment costs of these waters have increased due to stricter quality specifications, especially in the content of suspended solids and emulsified oils, which should be eliminated to minimum levels (less than 5 ppm). In the same way, in the increase of the volumes to be treated, which have elevated –in some cases- more than 100 times. Considering the industrial results obtained, we observed that the application in this flotation process in production fields is a valuable treatment alternative, with advantages over the conventional processes, in terms of efficiency, energy, financial and of process.